2019
DOI: 10.1177/2055207619845448
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ participation in their healthcare: A sociomaterial investigation of a diabetes app

Abstract: Objective This article explores how a diabetes app called Diapplo affected adolescents’ participation in their healthcare by investigating adolescents’ meaning-making in relation to their use of the app. Methods Using a qualitative single case-study design, we adopted a multimethod responsive approach to data generation that included written data from the app development process, individual and group interviews and observations of the adolescents in the clinical situati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…If the application can collect data automatically and promptly without users’ frequent input, and be compatible with other devices and platforms (e.g., blood glucose-related applications and blood glucose monitors (or blood glucose pumps) [ 52 ], mobile phones and tablet computers, and Apple and Android systems [ 6 ]), it will enhance the use efficiency and affect the degree of user utilization and the willingness to use it continuously [ 50 ]. However, healthcare practitioners believe that heavy offline workloads restrict their time and effort to learn, adapt to, and use the application, even if they approve of it [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…If the application can collect data automatically and promptly without users’ frequent input, and be compatible with other devices and platforms (e.g., blood glucose-related applications and blood glucose monitors (or blood glucose pumps) [ 52 ], mobile phones and tablet computers, and Apple and Android systems [ 6 ]), it will enhance the use efficiency and affect the degree of user utilization and the willingness to use it continuously [ 50 ]. However, healthcare practitioners believe that heavy offline workloads restrict their time and effort to learn, adapt to, and use the application, even if they approve of it [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, this is not only an issue in the case of complex chronic conditions such as spinal cord injury, but it can also be relevant for chronic conditions with relatively more straightforward self-management requirements, such as diabetes. For instance, in their study about a diabetes self-management app for adolescents, Ledderer, Møller and Fage-Butler (2019) showed how sometimes barriers to its use were due to there being an incompatibility between the app and how the adolescents wanted to live their lives. For example, some adolescents in the study reported preferring to spend time outside with friends or interacting on social media rather than typing in blood glucose measurements in the app.…”
Section: The Missing Existential Perspective and The Lack Of Integrat...mentioning
confidence: 99%
“…Social app platforms have also been considered for better understanding and treating T1D in youths in their daily lives. For example, a study found that participants wanted to incorporate a social platform in a diabetes decision tool app [288], whereas another study used the Instagram social platform as a tool to collect data about what T1D looks like in daily life [289]. However, it is important to note that youth with T1D could also potentially feel pressured or discouraged by social media if they observe others posting about perfect blood glucose levels if they do not obtain similar readings.…”
Section: Using Smartphone Apps and Phone-based Systems To Improve T1dmentioning
confidence: 99%